Do the Amazon and Orinoco freshwater plumes really matter for hurricane‐induced ocean surface cooling?. Issue 4 (1st April 2016) - Hernandez, O.; Jouanno, J.; Durand, F.
ABSTRACT: Recent studies suggested that the plume of low‐saline waters formed by the discharge of the Amazon and Orinoco rivers could favor Atlantic Tropical Cyclone (TC) intensification by weakening the cool wake and its impact on the hurricane growth potential. The main objective of this study is to quantify the effects of the Amazon‐Orinoco river discharges in modulating the amplitude of TC‐induced cooling in the western Tropical Atlantic. Our approach is based on the analysis of TC cool wake statistics obtained from an ocean regional numerical simulation with ¼º horizontal resolution over the 1998–2012 period, forced with realistic TC winds. In both model and observations, the amplitude of TC‐induced cooling in plume waters (0.3–0.4ºC) is reduced significantly by around 50–60% compared to the cooling in open ocean waters out of the plume (0.6–0.7ºC). A twin simulation without river runoff shows that TC‐induced cooling over the plume region (defined from the reference experiment) is almost unchanged (∼0.03ºC) despite strong differences in salinity stratification and the absence of barrier layers. This argues for a weaker than thought cooling inhibition effect of salinity stratification and barrier layers in this region. Indeed, results suggest that haline stratification and barrier layers caused by the river runoff may explain only ∼10% of the cooling difference between plume waters and open ocean waters. Instead, the analysis of the background oceanic conditions suggests that the regional distribution of the thermal stratification is the main factor controlling the amplitude of cooling in the plume region. Key Points: Amplitude of TC‐induced cooling is significantly reduced in Amazon and Orinoco plume regions Cooling difference between plume and open ocean waters are almost not sensitive to river runoff Thermal stratification is at leading order the main factor controlling the amplitude of cooling